PIK3CA Amplification Is Common in Left Side-Tubular Adenomas but Uncommon Sessile Serrated Adenomas Exclusively with KRAS Mutation - Lee, Hyunsu (Int J Med Sci, 2015)
Colorectal cancer is a heterogeneous disorder than arises via multiple distinct pathways, from tubular adenomas (TAs) and sessile serrated adenomas (SSAs), which are clinically, morphologically, and molecularly different. We examined PIK3CA amplification in colorectal precancerous legions, including TAs and SSAs. DNA was isolated from paired normal and tumoral tissues in 64 TAs and 32 SSAs. PIK3CA amplification, KRAS mutation, and BRAF mutation were analyzed by real-time PCR and pyrosequencing. PIK3CA amplification was found in 25% of TAs and 9.4% of SSAs, respectively. KRAS and BRAF mutations were mutually exclusive in both TAs and SSAs. In TAs, PIK3CA amplification was associated with left side and it was mutually exclusive with KRAS mutation. These results suggest that PIK3CA amplification may be early and important event in colorectal carcinogenesis and may drive the development of left-side TAs independently with KRAS mutation.